Spin Caloritronic Transport of 1,3,5-Triphenylverdazyl Radical - 吴秋华 赵朋 刘德胜 (Chinese physics letters, 2016)
We investigate theoretically the spin caloritronic transport properties of a stable 1,3,5-triphenylverdazyl （TPV） radical sandwiched between Au electrodes through different connection fashions. Obvious spin Seebeck effect can be observed in the para-eonnection fashion. Furthermore, a pure spin current and a completely spin-polarized current can be realized by tuning the gate voltage. Furthermore, a 100% spin polarization without the need of gate voltage can be obtained in the meta-conneetion fashion. These results demonstrate that TPV radical is a promising material for spin caloritronic and spintronic applications.